Determinants of Tax Regulations Referring to ESG Principles on Company Performance in Indonesia - Silalahi, Heriantonius; Maulana, Nandi; Kurnia, Budi (Journal Economic Business Innovation, 2024)
Purpose: This study examines ESG integration in Indonesia's tax regulations and their impact on financial performance, focusing on green investments.Method: This study uses a qualitative case study method to analyze ESG integration in Indonesia's tax regulations, focusing on policies, carbon tax effectiveness, and emissions disclosure. The research is based on corporate legitimacy and institutional theories to explore the relationship between tax regulations and sustainable practices.Findings: The study's findings reveal significant growth in green investments in Indonesia, largely driven by supportive ESG-oriented tax policies. Despite this progress, challenges such as limited corporate awareness and data availability remain barriers to fully realizing the potential of these policies. The analysis also highlights the importance of these regulations in fostering sustainable business practices, particularly in industries like palm oil that are crucial for addressing climate change.Novelty: This research uniquely examines the impact of ESG-focused tax regulations on green investments and sustainable practices in Indonesia, using corporate legitimacy and institutional theories. It fills a literature gap by exploring how tax regulations drive ESG integration in the business sector of a developing country.Implications: The study has important implications for policymakers, businesses, and stakeholders in Indonesia and similar economies. It shows that ESG-focused tax policies positively impact green investments, suggesting that refining and implementing these policies could strengthen sustainable business practices and support environmental goals. The study also emphasizes the need for greater corporate awareness and better data collection to address challenges and ensure effective ESG integration in the corporate sector.